Digital Marketing Communication Model of Trendy Noodle Station @youneedmie.official - Daniel Susilo; Harliantara (Formosa Journal of Social Sciences (FJSS), 2023)
This study examines a digital marketing communication model utilized by Trendy Noodle Station @youneedmie.official, a Micro, Small and Medium Enterprises (MSMEs) in Indonesia. This study is driven by the increasing prevalence of micro, small, and medium enterprises (MSMEs) in Indonesia, with a specific focus on Warmindo (Warung Mie Indonesia or Indonesian Noodle Stall). Warmindo offers employment prospects for persons who are currently unemployed, enabling them to generate income. This study examines the context and significance of micro, small, and medium enterprises (MSMEs) within the economic framework of Indonesia. It highlights the inherent characteristics of MSMEs, such as their simplicity and adaptability, which facilitate self-management.The author used Krippendorf's content analysis approach to investigate the role of micro, small, and medium enterprises (MSMEs) in facilitating self-employment opportunities for those who are currently unemployed. This approach enables a methodical analysis of the several facets pertaining to the digital marketing methods employed by @youneedmie.official. The results of the study demonstrate the efficacy of digital marketing communication techniques in augmenting consumer engagement and improving sales performance.  The findings of this study indicate that the adoption of a professional digital marketing communication strategy can have a substantial positive impact on the business performance of micro, small, and medium enterprises (MSMEs)